Monitoring of Endangered Freshwater Mussels in Sweden Using Digital PCR - Per Sundberg; Alizz Axberg; Nauras Daragmeh; Niklas Wengström; Marina Panova (Environmental DNA)
ABSTRACT Freshwater mussels are traditionally monitored by visual observations which is time‐consuming and can be difficult depending on water conditions. Environmental DNA (eDNA) is an attractive alternative since it can detect a species in the water without visual observations. Furthermore, since the DNA can potentially travel downstream in the river systems, presence of a species can be detected even away from the population of mussels. In this paper, we evaluate and describe how dPCR (digital PCR) technique can be used to efficiently monitor four freshwater mussel species: the freshwater pearl mussel Margaritifera margaritifera from Margaritiferidae family and three species from Unionidae family: the depressed river mussel Pseudanodonta complanata, the painter's mussel Unio pictorum, and the thick shelled river mussel Unio crassus, which are all regarded endangered in many regions worldwide. dPCR assays for the four mussel species were developed and tested in silico before conducting field surveys. The verification step in the field was carried out in two Swedish rivers with confirmed populations of the freshwater pearl mussel (M. margaritifera). Furthermore, two other rivers with unknown presence of the endangered freshwater mussels were surveyed for occurrence of the four mussel species, using the capacity to multiplex several species simultaneously in a dPCR reaction. We furthermore showed that the target DNA concentrations probably depend on the season and water level, which may largely affect the detection probability and interpretation of the results in terms of population size.